2023
DOI: 10.1186/s12906-023-04107-4
|View full text |Cite
|
Sign up to set email alerts
|

Berberine improves inhibitory avoidance memory impairment of Toxoplasma gondii-infected rat model of ketamine-induced schizophrenia

Neghin Gholizadeh,
Abdolhossein Dalimi,
Fatemeh Ghaffarifar
et al.

Abstract: Background Memory impairment caused by Toxoplasma gondii infection has been documented. Berberine (BRB) is well known for its enhancing effects on memory and has shown promising results. However, the impact of BRB on T. gondii infection and schizophrenia-induced consolidation and reconsolidation memory impairment is still unclear. Here; we examined the effect of BRB on the inhibitory avoidance (IA) memory consolidation and reconsolidation impairment induced by T. gondii infection, and ketamine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…However, after acute dosing, psychiatric, psychotomimetic, cardiovascular, neurological, and other side-effects were more commonly observed after ketamine treatment than after placebo in patients with depression ( Short et al, 2018 ). Interestingly, one study showed Ber can inhibit avoidance memory impairment of Toxoplasma gondii-infected rat model of ketamine-induced schizophrenia ( Gholizadeh et al, 2023 ). Meanwhile, levo -tetrahydropalmatine, one of tetrahydroprotoberberines, could increase the bioavailability of ketamine and promote the metabolism of ketamine ( Du et al, 2020 ), so the combination of ketamine and Ber might be a valuable new idea.…”
Section: Discussionmentioning
confidence: 99%
“…However, after acute dosing, psychiatric, psychotomimetic, cardiovascular, neurological, and other side-effects were more commonly observed after ketamine treatment than after placebo in patients with depression ( Short et al, 2018 ). Interestingly, one study showed Ber can inhibit avoidance memory impairment of Toxoplasma gondii-infected rat model of ketamine-induced schizophrenia ( Gholizadeh et al, 2023 ). Meanwhile, levo -tetrahydropalmatine, one of tetrahydroprotoberberines, could increase the bioavailability of ketamine and promote the metabolism of ketamine ( Du et al, 2020 ), so the combination of ketamine and Ber might be a valuable new idea.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, astrocyte-derived EVs could promote recovery after IS by reducing the infarct volume, protecting the function of neuronal tracts, promoting axonal regeneration, and enhancing compound action potential recovery [123]. Recently, a large number of studies proved that berberine had neuroprotective effects on central nervous system diseases, including IS, AD, PD, and schizophrenia [124][125][126][127]. There are even two clinical studies on the efficacy of berberine in the treatment of schizophrenia (NCT02983188, NCT03548155: https://clinicaltrials.gov, accessed on 7 March 2024).…”
Section: Astrocyte-derived Evsmentioning
confidence: 99%
“…Ketamine significantly reduced the BDNF level in the hippocampus exhibiting a 3.5-fold reduction compared to the control animals (group I) (Table 8 and Figure 10e). The minimized levels of hippocampal BDNF caused by ketamine could result in synaptic plasticity loss as a possible mechanism for inducing schizophrenia [63]. The administration of formulations given to the animal groups III, IV, and V resulted in a considerable increase in the BDNF level by 1.7, 2.2, and 3.1 times, respectively, compared to rats treated with ketamine (group II).…”
Section: Groupmentioning
confidence: 99%